2016
DOI: 10.1016/j.matchar.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of yttrium-rich precipitates in a titanium alloy weld

Abstract: The yttrium-rich (Y-rich) precipitates that form in the fusion zone (FZ) of a Ti-5Al-1Sn-1Zr-1V-0.8Mo (wt.%) alloy, or Ti-5111, gas-tungsten arc welds (GTAW) were characterized. The filler metal was modified by a small concentration of Y in order to refine the microstructure and thus improve the FZ ductility. A high number density of nanoscale Y-rich precipitates were characterized in the weld FZ by atom probe tomography (APT) and scanning transmission electron microscopy (STEM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For example, APT studies have revealed the formation of α 2 precipitates of varying morphologies within the α case layer formed on Ti-6Al-4V [15] and have also investigated the relationship between mechanical properties and oxygen concentration in this alloy [16]. APT has also been used to study ordering [17][18][19], oxygen and carbon segregation [20] and fine scale precipitation [21][22][23] in a range of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, APT studies have revealed the formation of α 2 precipitates of varying morphologies within the α case layer formed on Ti-6Al-4V [15] and have also investigated the relationship between mechanical properties and oxygen concentration in this alloy [16]. APT has also been used to study ordering [17][18][19], oxygen and carbon segregation [20] and fine scale precipitation [21][22][23] in a range of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…oxygen and carbon segregation [18] and fine scale precipitation [19,20] in a range of titanium alloys.…”
Section: Introductionmentioning
confidence: 99%
“…This confirms the assumption that yttrium binds oxygen, thus increasing the stability of the supercooled b-phase upon cooling. 4,[8][9] Furthermore, such a behaviour resulted in a higher b-phase volume fraction, decreasing the hardness of the alloy. This was confirmed with the microhardness-indentation tests.…”
Section: Resultsmentioning
confidence: 99%
“…7 One of the most frequently employed alloying elements is yttrium. [8][9][10][11] Although it was already shown what microalloying of the Ti-4.8Al-1.2Mo-2.6V-0.6Cr-0.25Fe alloy with 0.06 % mass fraction of yttrium decreases the oxygen concentration in a-and b-solid solutions due to the formation of Y 2 O 3 particles, 4 detailed studies of a weld structure were not conducted. This is why our study aimed at investigating the influence of microalloying titanium alloys with zirconium and yttrium on the microstructure formation and mechanical properties of the weld joints of this alloy.…”
Section: Introductionmentioning
confidence: 99%
“…A good overview of the early use of atom probe on weld metals was given by Vitek and Babu [23]. In the last few years, atom probe tomography was mainly used to characterize the precipitation behavior of Cu-bearing pressure vessel steel welds [21,[24][25][26][27] or to study welds of more exotic materials like Y-rich Ti-5111 [28], friction stir welds of nanostructured ferritic alloys [29], or dissimilar metal welds [30].…”
Section: Introductionmentioning
confidence: 99%